Factors affecting the quality of life of the elderly in urban and rural areas to support the design for an aging society - Ongkananuwong, Sirisopa; Jarupan, Sarada (DEC Journal : Art and Design, 2023)
This study aims to compare and analyze theoretical concepts in research relating to the quality of life of the elderly and research on the space design for the quality of life of the elderly in urban and rural areas in Thailand to find out factors affecting the quality of life of the elderly in order to support the senior space designs for the elderly in Thai communities. The literature reviews are divided into two theoretical concepts: the quality of life of elderly people and theoretical ideas on spatial design for the elderly. The findings of these two groups of research are analyzed to gather the information needed to support the objectives of the study. The findings of this study revealed that there are similarities and differences between the elderly in the city and in the countryside that have an impact on the quality of life and the surface design that exists. Elderly people have consistent factors in both urban and rural areas: health factors, income problems, and a lack of caregivers. The distinctive characteristics of rural communities are higher than those of urban communities in terms of social activity, social participation, and family activities, but urban communities have better access to quality of life, health skills, and self-care than rural communities. It was found that the elderly had lots of accidents within the areas, both residential and religious, such as paths of houses, multi-level rooms, sliding materials and door geometry, parking, elderly and handicapped rest rooms, multi-level areas, roads, traffic paths of cars, and pedestrian paths. Therefore, communities should encourage community practitioners to support such areas to create sustainable communities for better quality of life for the elderly in the communities, and there should be a universal design theory that applies to older people and people with disabilities to be used as a design basis for communities. Cultural contexts that concern promoting the quality of life of the elderly, both physically and mentally, should be crucial points for further studies. Psychological factors play a crucial role in conducting spiritual preparations for the end of a person’s life. The research suggests that this is also the next challenge.